Analisis Kesadaran Pemilik Usaha Rumah Kos Terkait Pajak Hotel Kategori Rumah Kos Dalam Meningkatkan Penerimaan Pajak Hotel Daerah Jakarta Pusat Tahun 2020-2021 - Selvina Choirun Ni’mah; Bambang Irawan (Jurnal Ilmu Administrasi Publik, 2023)
This study aims to discuss the awareness of Boarding House business owners related to increasing hotel tax revenue in the Central Jakarta area in 2020-2021, as well as knowing what are the internal and external obstacles taxpayers in paying boarding house tax in the Central Jakarta area.this study uses a qualitative approach with descriptive research using data collection  techniques  in  the  form  of  interviews  to  obtain primary data and documentation, observation is done to obtain secondary data. Based on the results of this study, it can be seen that the awareness of Boarding House business owners related  to  hotel  tax  revenues  in  the  category  of  boarding houses in increasing hotel tax revenues in the Central jakarta area in fact from 2020 to 2021 has decreased for hotel tax objects in the category of boarding houses, although the boarding house business owners already understand, but they still cannot carry out their tax obligations due to lack of awareness from the public regarding the importance of paying hotel tax on  the category of boarding houses for local tax revenues in Central jakarta. One of the internal obstacles for taxpayers to pay boarding house taxes is the lack of awareness of taxpayers who register their businesses and also economic factors  caused  by  the  impact  of  the  pandemic.  While  the external constraints for socialization with taxpayers Boarding House has not been maximized, the lack of assertiveness of the government of Central Jakarta Regional Tax Service on the implementation or implementation of the boarding house tax so that there are still many boarding house business owners who shy away from their obligations and are not afraid of the sanctions that will be imposed